Towards a Political Mechanism for Enforcement of Union’s Values - Prostak, Rafał (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2017)
This research paper is a critical reflection on two attempts to fulfill the lack of an effective mechanism for monitoring and enforcing the Union’s values. The first attempt was made by J. W. Müller, who proposed to add a new body to Europe’s institutional system: the Copenhagen Commission. The second attempt originated from the European Parliament, which has urged the European Commission to submit, by September 2017, a proposal for the conclusion of the Union’s Pact for democracy, the rule of law and fundamental rights, in the form of an inter-institutional agreement.It is hard to predict if Müller’s Copenhagen Commission or the EP’s Pact will end up being incorporated into the Union’s system of values enforcement. Nevertheless, both attempts stand as clear proof that existing instruments are perceived as weak, and clearly point at the lack of elements that could make these instruments more effective. These are the main observations of the study.